Allogeneic hematopoietic stem cell transplant in pediatric acute myeloid leukemia: Lessons learnt from a tertiary care center in India. (3rd November 2020) - Arora, Shalabh; Pushpam, Deepam; Tiwari, Akash; Choudhary, Priyanshu; Chopra, Anita; Gupta, Ritu; Kumar, Rajive; Bakhshi, Sameer
Abstract: There is paucity of data on outcomes of MSD‐HSCT in children with relapsed or high‐risk AML from developing countries, which have unique challenges including adverse host factors and resource constraints. We retrospectively reviewed records of children (age ≤ 18 years) who underwent MSD‐HSCT for AML at our center from 2009 to 2019 to evaluate clinical outcome and its predictors using Cox proportional hazards model. There were 46 children (36 boys and 10 girls) with mean age 10.7 ± 4.8 years. Indication for HSCT was relapsed AML in CR2 (n = 37), primary refractory (n = 3), or relapsed refractory disease (n = 3); high‐risk (n = 1) or secondary (n = 2) AML in CR1. Five‐year EFS and OS were 33.3 ± 7.2% and 36.3 ± 7.6%, respectively. On multivariate analysis, CR1 duration less than 12 months, presence of active disease at transplant, and use of bone marrow stem cell graft were associated with poorer EFS and OS. There was one (2.2%) TRM, while disease relapse occurred in 20/40 patients who underwent HSCT in remission. Though the 5‐year EFS and OS were inferior to results reported from high‐income countries, relapse (and not TRM) was the major cause of treatment failure. A well‐sustained CR1, achievement of disease remission, and use of peripheral blood allograft seem imperative to a successful transplant. Targeted therapy along with HSCT may be the option for those with early relapse.